From Deep-Level Similarity to Subordinate Moqi: The Mediating Role of Leader-Member Exchange - Li, Lan; Zheng, Xingshan; Sun, Siwei (Frontiers in Psychology, 2022)
Fostering subordinate moqi is a significant method to improve the cooperating quality and promote positive outcomes. However, little is known about the influencing factors and mechanisms of subordinate moqi. To address this issue and explore the influencing factors of subordinate moqi, we draw on self-categorization theory to develop a mediation model to examine whether and how deep-level similarity affects subordinate moqi, casting the leader-member exchange (LMX) as a mediator. A two-wave online survey was conducted and 316 data was collected. A Structure Equation Modeling analysis was used to test all hypotheses with Mplus 7. Results showed that the deep-level similarity could positively predict subordinate moqi and LMX, respectively. Additionally, LMX was a significant predictor of subordinate moqi as well as it mediated the positive relationships between deep-level similarity and subordinate moqi. These findings expand our understanding of the antecedents of subordinate moqi. It is suggested that developing subordinates’ deep-level similarity with supervisors and LMX relationships are instrumental in cultivating subordinate moqi which promote positive outcomes. Organizations should integrate effective management programs into managerial strategies to enhance deep-level similarity and LMX, in turn, fosters subordinate moqi.